It's Your Time Activate Your Faith, Achieve Your Dreams, and Increase in God's Favor - Osteen, Joel (New York, NY Free Press, 2009)
Shares a message of hope and inspiration for using one's faith as a cornerstone to build a happy, secure, and fulfilled life.
Keywords: Christian life. Spiritual life -- Christianity